Neolignans, styrylpyrones and flavonoids from an Aniba species - Rossi, M. H.; Yoshida, M.; Maia, JGS (Elsevier B.V., 1997)
The trunk wood and barks from an Aniba species contain four esters of benzoic acid with cinnamyl alcohol, five benzofuran neolignans, licarin-A, burchellin, cis-burchellin, burchellin-rearranged and cis-burchellin-rearranged, one tetrahydrofuran neolignan, aristolignin, three bicyclooctane guianin-type neolignans, (7S, 8S, 1'R, 5'R)-4-hydroxy-3,3'-dimethoxy-4',6'-dioxo-8.1', 7.5'-neolignan-Delta: 1,3,5,2',8' and the new (7S, 8S, 1'R, 4'R, 5'S)-4'-hydroxy-3,4,3'-trimethoxy-6'-oxo-8.1', 7.5'-neolignan-Delta: 1,3,5,2',8' and (7S, 8S, 1'R, 4'R, 5'S)-4,4'-dihydroxy-3,3'-dimethoxy-6'-oxo-8.1', 7.5'-neolignan-Delta: 1,3,5,2',8', one new bicyclooctane canellin-type neolignan (7S, 8S, 1'S, 4'R, 5'R, 6'S)-4',6'-dihydroxy-3,4-dimethoxy-3'-oxo-8.1', 7.5'-neolignan-Delta: 1,3,5,8', two styrylpyrones, 4-methoxy-6-(11,12-dimethoxy-trans-styryl)-2-pyrone and 6-(11,12-methylenedioxy-trans-styryl)-4-methoxy-2-pyrone, two styrylpyrone dimers: 4'-methoxy-8-(11,12-dimethoxyphenyl)-7-[6-(4-methoxy-2-pyronyl)-6-(E)-styryl-1'-oxabicyclo[4,2,0]octa-4'-en-2'-one and the new 11,12-dimethoxyphenyl-7,7'-di-[6-(4-methoxy-2-pyronyl)]-cyclobutane and six flavonoids, 3,5-dihydroxy-7,4'-dimethoxyflavone, 5-hydroxy-3,7,4'-trimethoxyflavone, 3,5,4'-trihydroxy-7-methoxyflavone, 2,3-dihydro-5-hydroxy-7,4'-dimethoxyflavone, 2,3-dihydro-3,5-dihydroxy-7-methoxyflavone, 2,3-dihydro-3,5-dihydroxy-7,4'-dimethoxyflavone and a new flavan, 6,7,3',4',5'-pentamethoxyflavan. (C) 1997 Elsevier B.V. Ltd.
Keywords: Aniba sp; Lauraceae; neolignans; trunk wood; bark; styrylpyrones; flavonoids